Evaluation of research performed on energy efficiency in energy-intensive manufacturing companies - Knayer, Tobias; Kryvinska, Natalia (Frontiers in Energy Research, 2022)
The implementation of climate protection cannot succeed without increasing energy efficiency in companies. Increasing energy efficiency is an important success factor for the energy transition, but unfortunately the energy saving potentials are only insufficiently exploited. The aim of this paper is therefore to highlight the current state of research on energy efficiency potentials in companies at the technology level. For this purpose, an extensive literature search was conducted with more than 30 keywords. After screening and cleaning, 101 papers were selected and reviewed in detail. The literature search was performed using eight evaluation criteria: Origin and year of publication, type of company, type of industry, type of data, survey method, number of participants, data collection method, and analysis method. In order to evaluate the statements and results of the considered works, a SWOT analysis was used. Our analysis revealed that: (1) studies explicitly addressing energy efficiency measures and potentials at the technology level are scarce. Even fewer papers address the relationships and interactions (positive or negative) between individual measures; (2) most studies focus on large and manufacturing companies, most of which are energy-intensive. SMEs in the non-manufacturing sector, such as trade, commerce and services, are far less represented; (3) the chosen research focus and content is often - barriers, drivers, and theory models for energy efficiency, and secondary data are mostly used. Of the studies that considered primary data, 71% used a questionnaire survey. Research into the interactions between individual measures enables policymakers to target business support programs.